A Group of Eleventh Graders’ Life Stories: Reconstructing Social Identity - Peñaloza Villamizar, Josefina (Universidad Pedagógica y Tecnológica de Colombia, 2017)
This qualitative and interpretive study aimed to analyze how a group of eleventh graders reconstructed their social identity through life stories and writing related tasks in their native language. This notion is supported in professional literature: “Constructing and reconstructing identity through narratives is like giving sense to the life;” “It is like reorganizing the story lived,” (Park & Burgess, 1924, p. 4). “It is like trying to assume what has happened with the lives and turn them into stories,” (Hardy, 1968, p. 9). The Reconstruction of identity can be expressed through language learning in the way students use narratives; such narratives can provide a glimpse into students’ private world, (Pavlenko, 2007). The instruments from which data was collected were life stories and interviews. The four participants reconstructed their identity with descriptions of overcoming abuse and mistreatment, fighting to survive and to continue ahead, and creating a better life.